Self-Regulation Test-Taking Strategies for Mathematics - Kiew Nee Tee; Kwan Eu Leong; Suzieleez Syrene Abdul Rahim (MUST: Journal of Mathematics Education, Science and Technology, 2018)
The present study aims at exploring various self-regulation test-taking strategies used by the grade 11 students for their mathematics tests which is observed from three aspects, they are before, during, and after test-taking. The data were collected from 86 students in a private school which located in Malaysia. The goal-setting and planning, help-seeking, seeking information, rehearsal, memorization, reviewing, peer pressure, adult influence, self-consequences, self-motivated, and environment setting were the strategies that is used for test preparation. Outline formulas, recall and identify key information, keep trying, and checking were the strategies used during test-taking. In addition, correction and self-evaluation were the strategies used after the test-taking. The study further examined differences of various test-taking strategies used across three performance groups, high, medium, and low achievers, and also for male and female students. The results showed that there were statistical differences in goal-setting and planning, help-seeking, keep trying, checking, and correction strategies among high, medium, and low achievers. There were also statistical differences in goal-setting and planning, rehearsal, self-motivated, outline formulas, checking, and correction strategies between male and female students. The result of this research showed that the groups of using goal-setting and planning, rehearsal, help-seeking, recall and identify key information, keep trying, checking, and correction strategies have higher scores in mathematics performance rather than those groups which do not use these strategies.